Ответы и объяснения

2013-04-09T17:28:19+00:00

а)

x^2-3x-4<=0

x^2-3x-4=0

D=(-3)^2-4*1*(-4)=9+16=25

x1,2=3+-5/2

x1=3+5/2=4

x2=3-5/2=-1

б)

2x^2+5x/x^2+5x+4 >=1

2x^2+5x>=1

2x^2+5x-1=0

D=5^2-4*2*(-1)=25+8=33

x1,2=-5+-33/4

x1=-5+33/4=7

x2=-5-33/4=-7

 

x^2+5x+4>=1

x^2+5x+4-1=0

x^2+5x+3=0

D=5^2-4*1*3=25-12=13

x1,2=-5+-13/2

x1=-5+13/2=4

x2=-5-13/2=-9

в)

f(x)=Vx^2+7x+12/x

(Vx^2+7x+12/x)^2

x^2+7x+12/x=0          x=0

x^2+7x+12=0

D=7^2-4*1*12=49-48=1

x1,2=-7+-1/2

x1=-7+1/2=-3

x2=-7-1/2=-4